Effect of tissue viscoelasticity on delivered mechanical power in a physical respiratory system model: distinguishing between airway and tissue resistance - Walzel, Simon; Roubik, Karel (Biomedical physics & engineering express, 2024)
Understanding the mechanics of the respiratory system is crucial for optimizing ventilator settings and ensuring patient safety. While simple models of the respiratory system typically consider only flow resistance and lung compliance, lung tissue resistance is usually neglected. This study investigated the effect of lung tissue viscoelasticity on delivered mechanical power in a physical model of the respiratory system and the possibility of distinguishing tissue resistance from airway resistance using proximal pressure measured at the airway opening. Three different configurations of a passive physical model of the respiratory system representing different mechanical properties (Tissue resistance model, Airway resistance model, and No-resistance model) were tested. The same volume-controlled ventilation and parameters were set for each configuration, with only the inspiratory flow rates being adjusted. Pressure and flow were measured with a Datex-Ohmeda S/5 vital signs monitor (Datex-Ohmeda, Madison, WI, USA). Tissue resistance was intentionally tuned so that peak pressures and delivered mechanical energy measured at airway opening were similar in Tissue and Airway Resistance models. However, measurements inside the artificial lung revealed significant differences, with Tissue resistance model yielding up to 20% higher values for delivered mechanical energy. The results indicate the need to revise current methods of calculating mechanical power delivery, which do not distinguish between tissue resistance and airway flow resistance, making it difficult to evaluate and interpret the significance of mechanical power delivery in terms of lung ventilation protectivity.
Keywords: dýchací soustava; physical respiratory system model; Airway Resistance; biologické modely; umělé dýchání; Lung Compliance; Lung; viscoelasticity; Respiratory Mechanics; tissue resistance; mechanical ventilation; Respiratory System; Elasticity; lidé; pružnost; tlak; Models, Biological; mechanika dýchání; mechanical power; rezistence dýchacích cest; plíce; viskozita; poddajnost plic; Viscosity; Respiration, Artificial; Pressure; Humans